2019
DOI: 10.1186/s12903-019-0787-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation modelling for associated factors with dental caries among 3–5-year-old children: a cross-sectional study

Abstract: Background The aim of the current study was to explore the factors influencing dental caries among 3–5-year-old children in Sichuan Province and the interrelationship between these factors using structural equation modelling (SEM). Methods A cross-sectional study was conducted among 2746 3–5-year-old children in Sichuan Province. Examination of caries was conducted on all children and a questionnaire was answered by the children’s caregiver. SEM alternative models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…This cross-sectional study was a part of the Fourth National Oral Health Survey in China [27][28][29]. It was a school-based survey conducted from 07/01/2015 to 09/ 17/2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cross-sectional study was a part of the Fourth National Oral Health Survey in China [27][28][29]. It was a school-based survey conducted from 07/01/2015 to 09/ 17/2016.…”
Section: Methodsmentioning
confidence: 99%
“…Sichuan Province is located in western China and represents one of the largest provinces with regard to area and population [27,28]. A complex, multi-stage sampling design [27][28][29] was used to select participants who were representative of the province's population. In the first stage, six regions (Guang'an District, Chuanshan District, Jinniu District, Da County, Yibin County and Pi County) were obtained from 181 regions with probability-proportional-to-size (PPS) method ( Fig.…”
Section: Survey Samplingmentioning
confidence: 99%
“…Children with caregivers who possess positive health‐oriented attitudes had better oral hygiene practices and oral health . One Chinese study found a significant relationship between parental knowledge and attitudes and a family's dietary patterns . Children from socially deprived families had more dental decay than those from families of higher social status .…”
Section: Introductionmentioning
confidence: 99%
“…To explore the factors associated with toothache, we proposed an alternative model of the multifaceted relationship of parent education, residential area, socio-economic status (SES), parent awareness regarding children’s health conditions and food consumption frequency, and tooth brushing behaviour/frequency with the outcome (toothache) based on previous theoretical frameworks for dental caries 17 19 . Thus, we determined the direct and indirect relationships between toothache and its associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we determined the direct and indirect relationships between toothache and its associated factors. We assumed that parent awareness regarding children's health conditions and food consumption frequency 17 and tooth brushing behaviour/frequency 20 were the predictors of toothache. These factors were affected by SES 17,20 .…”
mentioning
confidence: 99%